2018
DOI: 10.47414/np.26.2018.211207
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between leaf area, above-ground mass and morphometric indices in miscanthus

Abstract: To establish varietal characteristics of yield formation in grain sorghum as affected by row spacing and fertilization system. Methods. The field experiment was carried out during the 2015-2017 period in a multifactorial stationary experiment in LLC Biotech LTD located in the central part of Boryspil district (Kyiv region) of the Left-Bank Forest-Steppe of Ukraine. Experiment design: factor Ahybrid: 'Lan 59', 'Burgo F1', 'Briggo F1'; factor Bdose of nitrogen fertilizers: N60P60K60 (control), N60P60K60 + N20, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The soil contamination's negative impact was neglected when biochar was incorporated into the system; the plant height in September for cases B and C was similar to A in the presence of B1 and B2. The morphological characteristics of M. × giganteus when the plant was cultivated in the traditional agricultural land showed a close correlation between height and weight of the shoots, numbers of leaves in each shoot and surface of the leaves [69]. Current research confirmed this correlation (Figure 3, Figure 4 and Figure S1) when an essential impact of the soil contamination on the morphological parameters was detected.…”
Section: Impact Of Soil Contamination By Diesel To M × Giganteus Biop...supporting
confidence: 56%
See 1 more Smart Citation
“…The soil contamination's negative impact was neglected when biochar was incorporated into the system; the plant height in September for cases B and C was similar to A in the presence of B1 and B2. The morphological characteristics of M. × giganteus when the plant was cultivated in the traditional agricultural land showed a close correlation between height and weight of the shoots, numbers of leaves in each shoot and surface of the leaves [69]. Current research confirmed this correlation (Figure 3, Figure 4 and Figure S1) when an essential impact of the soil contamination on the morphological parameters was detected.…”
Section: Impact Of Soil Contamination By Diesel To M × Giganteus Biop...supporting
confidence: 56%
“…The number of M. × giganteus leaves was connected with their surface having a correlation coefficient equal to 7.76 ± 0.07 [69]. The M. × giganteus leaves' surface was calculated using the approach described at Kvak et al [70] and presented in Figure 4.…”
Section: Impact Of Soil Contamination By Diesel To M × Giganteus Biop...mentioning
confidence: 99%